2013
DOI: 10.1115/1.4023849
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Constraint Effects on the Slitting Method for Measuring Residual Stress

Abstract: The incremental slitting or crack compliance method determines a residual stress profile from strain measurements taken as a slit is incrementally extended into the material. To date, the inverse calculation of residual stress from strain data conveniently adopts a two-dimensional, plane strain approximation for the calibration coefficients. This study provides the first characterization of the errors caused by the 2D approximation, which is a concern since inverse analyses tend to magnify such errors. Three-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Stress is then calculated from strain versus cut depth data using an elastic inverse [27], with Tikhonov regularization to smooth the stress by penalizing its second derivative [28]. The correction scheme by Aydiner and Prime [29] was used to accurately reflect the finite thickness of the slice by slightly altering a stress analysis that was based upon a plane strain finite element model. Each slitting measurement introduces a new stress-free surface, which will redistribute the stress in the body.…”
Section: Measurement Approachmentioning
confidence: 99%
“…Stress is then calculated from strain versus cut depth data using an elastic inverse [27], with Tikhonov regularization to smooth the stress by penalizing its second derivative [28]. The correction scheme by Aydiner and Prime [29] was used to accurately reflect the finite thickness of the slice by slightly altering a stress analysis that was based upon a plane strain finite element model. Each slitting measurement introduces a new stress-free surface, which will redistribute the stress in the body.…”
Section: Measurement Approachmentioning
confidence: 99%
“…Lastly, since the compliance matrix is computed using a plane strain model, it was scaled using the correction scheme developed by Aydiner and Prime [26] to account for the finite thickness of the slice.…”
mentioning
confidence: 99%
“…The aluminum T351 temper indicates solution heat treat followed by rapid quenching and then plastic stretching of 1-3% in the rolling (R) direction for residual stress relief (Prime and Hill, 2002). Slitting method (Aydiner and Prime, 2013;Cheng and Finnie, 2007;DeWald et al, 2004;Hill, 2013;Schindler, 1990) tests on the asreceived plate showed that the residual stresses had magnitudes of 10 MPa or less in both in-plane directions. Grain morphology was estimated from metallographic cross sections, which revealed pancake-shaped grains with typical dimensions of 30 m in the through-M A N U S C R I P T Prime, Page 6 thickness (TT) direction, 340 m in the rolling direction, and 160 m in the long transverse direction.…”
Section: Specimen and Materialsmentioning
confidence: 98%